ERROR ANALYSIS IN INTERMEDIATE STUDENTS OF ENGLISH FIRST (EF) DELTA PLAZA SURABAYA WRITING TEST - Daristin, Pipit Ertika (Jurnal Bahasa Inggris, 2017)
The main purpose of this article is to discuss the importance of error analysis in the teaching of English as a foreign language. Although errors are bad things in learning English as a foreign language, error analysis is advantageous for both learners and teachers. For learners, error analysis is needed to show them in what aspect in grammar which is difficult for them, whereas for teachers, it is required to evaluate them whether they are successful or not in teaching English. In this article, the writer presented some English sentences containing grammatical errors. These grammatical errors were analyzed based on the theories presented by the linguists. This analysis aimed at showing the students the causes and kinds of the grammatical errors. By this way, the students are expected to increase their knowledge on the English grammar.